Characterization and evaluation of antioxidant properties of leaf extracts from Rhododendron arboreum - Shobha Mehra; Ufondu Maryann Afoma; Namrata Dudha; Shilpy Singh; Shweta Sharma; Ved Vrat Verma; Mohammad Zuhaib; Varun Kumar Sharma (Journal of BioScience and Biotechnology)
Phytochemicals have been known to suppress the microbial activity and oxidative stress, which indicates the significance of plant material as anti-microbial and antioxidant agent. In this light the current study is worked out to screen the phytochemicals from the Rhododendron arboretum leaf extract and characterize it using HPLC. The alkaloids and flavonoids are the major secondary metabolites found during screening. Further, anti-oxidant properties of leaf extract of R. arboreum prepared in different solvent (methanol, ethyl acetate, petroleum ether, and chloroform) were analyzed using DPPH and FRAP assay. Observation of the present study indicates that methanolic extracts was found to show significant anti-oxidant activity with the IC50 value of 241.2 µg/ml and 163.6 µg/ml in DPPH and FRAP assay respectively. In conclusion, the leaf extracts of R. arboretum can be one of the better natural source of antioxidant source and could be used for therapeutic purpose in the treatments of different diseases.